Understanding Muslim Identity: Rethinking Fundamentalism By Gabriele Marranci (Hampshire, UK: Palgrave Macmillan, 2009. 242 pages.) (American Journal of Islam and Society, 2010)
Gabrielle Marranci seeks to shift the analyses of “Islamic fundamentalism/radicalism” discourses away from those focusing on cultural and politicalessentialism, scripturalism, and social determinism and toward that ofexploring the dynamics of radicalization by examining the central role ofemotions on identity formation. His main thesis is that fundamentalismmust be understood as a process linked to identity and identification (nota thing) and that theories which take into account the crucial role of emotions,feelings, and the environment can explain fundamentalism, includingIslamic fundamentalism, more accurately then social deterministand/or cultural constructivist theories can (pp. 77-80). The author thus setsout to “engage with an incredibly expanding academic literature [onIslamic fundamentalism] that tends to treat religious fundamentalism onthe basis of culturalist or social theory discourse” (p. 153). He uses thesame analytical lens adopted in his Jihad beyond Islam (London: Berg,2006) ...